Acute stress alters probabilistic reversal learning in healthy male adults - Wieland, Lara; Ebrahimi, Claudia; Katthagen, Teresa; Panitz, Martin; Luettgau, Lennart; Heinz, Andreas; Schlagenhauf, Florian; Sjoerds, Zsuzsika (The European journal of neuroscience, 2023)
Behavioural adaptation is a fundamental cognitive ability, ensuring survival by allowing for flexible adjustment to changing environments. In laboratory settings, behavioural adaptation can be measured with reversal learning paradigms requiring agents to adjust reward learning to stimulus–action–outcome contingency changes. Stress is found to alter flexibility of reward learning, but effect directionality is mixed across studies. Here, we used model‐based functional MRI (fMRI) in a within‐subjects design to investigate the effect of acute psychosocial stress on flexible behavioural adaptation. Healthy male volunteers (n = 28) did a reversal learning task during fMRI in two sessions, once after the Trier Social Stress Test (TSST), a validated psychosocial stress induction method, and once after a control condition. Stress effects on choice behaviour were investigated using multilevel generalized linear models and computational models describing different learning processes that potentially generated the data. Computational models were fitted using a hierarchical Bayesian approach, and model‐derived reward prediction errors (RPE) were used as fMRI regressors. We found that acute psychosocial stress slightly increased correct response rates. Model comparison revealed that double‐update learning with altered choice temperature under stress best explained the observed behaviour. In the brain, model‐derived RPEs were correlated with BOLD signals in striatum and ventromedial prefrontal cortex (vmPFC). Striatal RPE signals for win trials were stronger during stress compared with the control condition. Our study suggests that acute psychosocial stress could enhance reversal learning and RPE brain responses in healthy male participants and provides a starting point to explore these effects further in a more diverse population. In this study, we investigated the effect of acute psychosocial stress on flexible behavioural adaptation using a reversal learning task during fMRI scanning and after a Trier Social Stress Test in 28 healthy male participants. We found a small improving effect on task performance accuracy, which was best explained by Rescorla–Wagner double updating in our computational modelling approach. At the neural level, we saw that striatal reward prediction error signal for win trials was stronger during the stress compared with the control condition.